Synthesis, Characterization and Luminescence of Gold Complexes Bearing an NHC Ligand Based on the Imidazo[1, 5‐a]quinolinol Scaffold. Issue 32 (19th September 2013) - Kriechbaum, Margit; Winterleitner, Gerda; Gerisch, Alexander; List, Manuela; Monkowius, Uwe
Abstract: We report on the synthesis and characterization of an NHC ligand based on the imidazo[1, 5‐ a ]quinolinol scaffold. The benzyl‐protected NHC precursor was used for the preparation of the corresponding Ag I, Au I and Au III complexes. The molecular structures of the Au I and Au III halide complexes determined by single‐crystal X‐ray diffraction reveal considerable distortion of the rigid NHC moiety due to steric repulsion between the gold and oxygen atoms. At ambient temperature, the complexes are weakly fluorescent from an intraligand excited state, whereas at 77 K the emission spectra are dominated by intraligand phosphorescence. Abstract : Silver(I), gold(I) and gold(III) complexes bearing an NHC ligand based on imidazo[1, 5‐ a ]quinolinol have been synthesized. The molecular structures of the gold complexes reveal distortion of the rigid NHC moiety due to steric repulsion between the gold and oxygen atoms. At room temperature, the complexes are weakly fluorescent, whereas at 77 K the emission spectra are dominated by phosphorescence.